Taxation - an instrument for achieving carbon dioxide emission reductions? - Kamm, Nadia (Department of Public Law, 2015)
The aim of this research project is to examine the adaptation of taxation systems as an instrument for achieving carbon dioxide (CO2) emission reductions.